Isolation and identification of microorganisms in biofilms from the Castillo de Chapultepec, Mexico City (Nexo Revista Científica, 2012)
Today microbiology is based on pure cultures and separate microorganisms, pure cultures really do not exist in nature, because that microorganism are combined into large colonies slimy (biofilms) in which the various individuals establish relationships and dependencies. Only in the United State of America is estimated that biofilms cause billions of dollars in energy losses, equipment damage, product contamination and medical infections. This paper presents the results of the isolation of microorganisms by microbiological and molecular methods, from biofilms located in the Castle of Chapultepec in Mexico City. In the biofilm coexist different genres of filamentous fungi such as Cladosporium, Mucor, Alternaria, Aspergillus, Aureobasidium, Rhodotorula and others in those biofilms; besides bacterial genera as Bacillus, Pantoea, Kokuria, etc. Many of these microbial genera have been widely reported as a participating in biodeterioration processes to monuments and others are reported as contributing to its restoration, so this work opens the door to future researches that allow biological restoration of monuments, conservation and development of new biotechnological processes.Keywords: Microbiology; pure cultures; biofilms; isolation of microorganism; microbiological methods; biodeterioration processes.DOI: http://dx.doi.org/10.5377/nexo.v24i2.656